Life table studies of rachiplusia nu(Guenée) and chrysodeixis (= Pseudoplusia) includes (Walker) (Lepidoptera: Noctuidae) on artificial diet - Barrionuevo, Maria Jose (2012)
Rachiplusia nu (Guenée) and Chrysodeixis (= Pseudoplusia) includens(Walker) (Lepidop-tera: Noctuidae) are 2 economically important species in soybean in northern Argentina. Life cycle, reproductive and population parameters of R. nuand C. includensreared on arti-ficial diet were determined under controlled environmental conditions. Fecundity increased from d 2 to 3 with values of 67.6 eggs per female for R. nuand 75.7 eggs for C. includens. An average of 79.9% (R. nu) and 74.4% (C. includens) of individuals reached the larval stage and 71.1% (R. nu) and 71.4% (C. includens) of individuals reached the adult stage. The life expectancy (ex) curve showed 4 and 3 periods of mortality. The survivorship curves of the 2 species resembled the theoretical type I. Life table analysis determined that R. nuand C. includens have the potential to quickly increase their populations under controlled rearing conditions. These results provide important information that will be used to improve artifi-cial rearing procedures contributing with biological studies towards to develop management programs of both species.